Left ventricular diastolic dysfunction in hypertension - Bamaiyi, Adamu Jibril (My University, 2019)
Heart failure with a preserved ejection fraction (HFpEF) accounts for half of all admissions for heart failure. However, there are no therapeutic approaches with proven benefits. Hypertension is a major risk factor for HFpEF, but the development of HFpEF may often occur in hypertensives irrespective of the degree of blood pressure (BP) control. Better insights into the identification of those at risk for and appropriate approaches to managing hypertensives at risk of HFpEF are therefore required. In the present thesis I assessed several aspects of the functional changes in the left ventricle (LV) (diastolic dysfunction [DD]), thought to antedate the development of hypertensive HFpEF. Patients with hypertensive heart disease and associated underlying coronary artery or other diseases, often require β-adrenergic receptor (AR) blocker therapy. However, whether sympathetic-induced β-AR stimulation (which often accompanies heart failure) has beneficial effects on LV diastolic function in those with hypertensive LV DD, is unknown. I therefore assessed the impact of acute administration of the β-AR stimulant, isoproterenol (ISO) on LV diastolic function in rat models of hypertension. As compared to normotensive rats, or Dahl salt sensitive (DSS) rats not receiving NaCl in the drinking water, Spontaneously Hypertensive (SHR) and DSS rats receiving NaCl in the drinking water had a reduced myocardial relaxation as indexed by lateral wall e’ (early diastolic tissue velocity at the level of the mitral annulus) and an increased LV filling pressure as indexed by E/e’. However, LV ejection fraction and deformation and motion were preserved in both SHR and DSS rats. The administration of ISO resulted in a marked increase in ejection fraction and decrease in LV filling volumes in all groups; and an increase in e’ in SHR, but not DSS rats. However, after ISO administration, although E/e’ decreased in DSS rats in association with a reduced filling volume, E/e’ in SHR remained unchanged. These data suggest that the hypertensive heart is indeed characterised by reductions in myocardial relaxation and increases in filling pressures, but β-AR activation fails to improve myocardial relaxation and when this occurs, does not reduce LV filling pressures.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, for the degree of Doctor of Philosophy
Keywords: Heart failure--Treatment; Heart failure, Congestive; Heart disease